A evoluç\~ao do valor adicionado doméstico nas principais regi\~oes do mundo - Marcelo José Braga Nonnenberg; Flavio Lyrio Carneiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This article proposes an alternative methodology to partially quantify the phenomenon of global value chains, analyzing the evolution of the domestic value-added content in exports of a number of medium and high technology products for three groups of developing countries - seven Asian, five European and ten from Latin America -, and three developed countries, for the period 1992-2013. The data permitted to draw some conjectures about the evolution of domestic value-added in the countries' exports. For the Asian countries in the sample, it was found that, in some of the analyzed chapters, most countries' indicators increased on the sample period. As for the developing countries of Europe, the indicators suggest an improvement of domestic value aggregation in a number of chapters, which seems to support the hypothesis that integration with leading countries in the region has opened opportunities for increasing productive capacity in these countries. As for the Latin American countries analyzed, the performance is clearly unfavorable; Mexico was the main highlight, with positive indicators in most chapters. The downward trend exhibited by Brazilian indicators in some chapters in recent years deserves to be emphasized. Taken together, the results suggest, with few exceptions, concern about the prospects of development of the industrial capacity of these Latin American countries.
Keywords: F1; 330; trade in value-added; global value chains; international production fragmentation